COMPARATIVE BIOCHEMICAL PROFILE OF GREEN VEGETABLES GROWN IN CONTROLLED AND POLLUTED WATER: Life Science - Biotechnology - JOSHI, NAVNEET (International Journal of Life Science and Pharma Research, 2018)
The biochemical profile of the green vegetables is being compared which is grown in controlled and polluted water of Drvyawati river, Jaipur. These biochemical attributes were studied on the basis of quantification of Ascorbic acid, Lipid, Protein, Starch, Total soluble sugars, Chlorophyll, Carotenoids and Nucleic acids (DNA/RNA). Two economically important plants namely Radish (Raphanus sativus L. var. Daikon, "Japani white") and Brinjal (Solanum melongena L. var. esculentum, "PPL/PPR") Omaxe hybrid seeds commercially supplied by Raunak Seeds Limited, New Delhi were taken as experimental material. In this article, the toxic effects of industrial effluents on the growth and various biochemical characteristics on these vegetables were studied. The outcome of quantitative analysis of primary metabolites and other biochemical characteristics in whole plants as well as fruits grown in control and polluted water conditions have suggested that the water quality is not suitable for irrigation and increases the level of toxicity in vegetable crops.